ANALISIS KINERJA PT. BPR BANK BOYOLALI DENGAN METODE RGEC - Ekowati, Dhiana; Mawar Sari, Defita; Kholisoh, Luluk; Isfaatun, Eliya; Magdalena PD, Maria ((JRAMB) Jurnal Riset Akuntansi Mercu Buana, 2024)
A bank is a financial intermediary institution, generally established with the authority to accept money deposits, lend money, and issue promissory notes or known as banknotes. Financial performance is one of the important indicators to determine the financial condition of the bank. The better the financial performance, the better or healthier the health level of the bank. (Sukarno, 2011: 2). This study aims to analyze banking health performance using the RGEC method. The financial ratios used in this study are LDR, CGC, ROA, BOPO, and CAR. The research object in this study is the financial performance report of PT BPR Bank Boyolali using the RGEC method for the final quarter period of 2021 - 2023. This type of research is descriptive quantitative, a research method that utilizes quantitative data and is described descriptively. This study uses secondary data in the form of financial information obtained from financial reports published through the Financial Services Authority (OJK) website. The results of this study indicate a decrease in the LDR ratio from 98% in 2021 to 79.9% in 2023, reflecting a more balanced management of loans and deposits. The implementation of Good Corporate Governance (GCG) principles remains good with high regulatory compliance. Profitability remains solid with a stable ROA at 2.5% in 2021 and 2022, albeit slightly declining to 2.3% in 2023, and an efficient BOPO ratio of 79.9% in 2021.